2016
DOI: 10.1016/j.jtusci.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Production of biogas from poultry litter mixed with the co-substrate cow dung

Abstract: Poultry litter (a mixture of rice hulls, sawdust and chicken excreta of broilers) mixed with the co-substrate cow dung and poultry droppings was evaluated under anaerobic conditions for the production of biogas (methane). Four laboratory scale reactors, R1, R2, R3 and R4, were set up with different proportions of waste poultry litter, cow dung and poultry droppings and had a 6% total solid concentration. Digestion was carried out for 50 days at room temperature, 32 ± 3 • C. Volatile solid degradation and speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 10 publications
0
24
1
Order By: Relevance
“…Poultry population in Bangladesh is estimated about 304.17 million where chicken population is about 255.31 million (Hamid et al, 2017). Also, it is estimated that approximately 1,560,000 metric tonnes of poultry waste is produced in Bangladesh each year (Miah et al, 2016). Analysis has shown that poultry litter contains potentially valuable plant and animal nutrients, including nearly 30 percent crude protein and high levels of minerals and some heavy metals (Zinn et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Poultry population in Bangladesh is estimated about 304.17 million where chicken population is about 255.31 million (Hamid et al, 2017). Also, it is estimated that approximately 1,560,000 metric tonnes of poultry waste is produced in Bangladesh each year (Miah et al, 2016). Analysis has shown that poultry litter contains potentially valuable plant and animal nutrients, including nearly 30 percent crude protein and high levels of minerals and some heavy metals (Zinn et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…By comparison, the optimum pH for AD is generally in the range 6.5 to 8.0 77,78 . It has been probed that if this parameter is regulated before and during AD, the methanogenesis process could be improved and better biogas production could be achieved 79 . The problem represented by the high pH of PL is closely related to the inhibition by N. During AD at high pH there is a shift of the equilibrium from free NH 3 to ionised (NH 4 + ) ammonia, which is identified as the main cause of inhibition 80 …”
Section: Main Biorefinery Processes Of Plmentioning
confidence: 99%
“…77,78 It has been probed that if this parameter is regulated before and during AD, the methanogenesis process could be improved and better biogas production could be achieved. 79 The problem represented by the high pH of PL is closely related to the inhibition by N. During AD at high pH there is a shift of the equilibrium from free NH 3 to ionised (NH 4 + ) ammonia, which is identified as the main cause of inhibition. 80 In order to minimise NH 3 inhibition, the use of treatments such as ammonia stripping 81,82 and dilution of the material to 0.5-3.0% TS have been recommended, 83 to increase the CH 4 yield of this residue.…”
Section: Biochemical Process: Admentioning
confidence: 99%
“…The fermentation process in which a variety of different substances are added and mixed is called co-fermentation. The range of waste with a potential application for the biogas production process is very extensive (Miah et al, 2016;Curkowski, Oniszk-Popławska, 2010). Substrates are used in various forms, volume ratios and at different temperatures during biogas production in a biogas plant.…”
Section: Introductionmentioning
confidence: 99%